The emerald handbook of smart cities in the gulf region : innovation, development, transformation, and prosperity for vision 2040 - Lytrans, Miltiadis D.; Alkhaldi, Afnan; Malik, Sawsan (Emerald Publishing Limited, 2024)
The Emerald Handbook of Smart Cities in the Gulf Region: Innovation, Development, Transformation, and Prosperity for Vision 2040 is a definitive reference edition that employs a four-tiered approach to understanding smart cities in the Gulf Region: Innovation, Development, Transformation, and Prosperity. This active learning approach empowers readers to apply a wide range of knowledge from social sciences and computer science to real-world issues, fostering critical thinking skills and competencies. Editors Miltiadis D. Lytras, Afnan Alkhaldi, and Sawsan Malik unite diverse communities of researchers, academics, practitioners, industrial managers, and policy makers to advance applied research, best practices, and lessons related to smart cities in the Gulf Region. This collected work uniquely integrates urban planning, advanced computational, and government policy-making aspects, with a focus on disseminating the momentum of Smart Cities Research in the Gulf Region. It addresses the comprehensive Smart Cities agenda, encompassing strategic, technical, computational, economic, social, and innovative dimensions. It delves into sophisticated computational technologies, such as AI, Blockchain, Metaverse, Cloud Computing, Data Mining, IoT, and more, emphasizing their role in realizing the vision of smart cities. Moreover, it addresses the social, economic, and sustainability dimensions of smart cities, touching on well-being, quality of life, social inclusion, and citizen engagement. This comprehensive study is suited for a wide-ranging audience, including researchers, academics, practitioners, industrial managers, and policy makers interested in advancing applied research, best practices, and lessons related to smart cities in the Gulf Region.
Includes index.
Keywords: City planning -- Persian Gulf.; Political Science -- Public Policy -- General.; Environmental policy and protocols.; Central, national, federal government policies.; elektronické knihy; electronic books